Diversity of Mushrooms and Their Metabolites of Nutraceutical and Therapeutic Significance. (10th January 2016) - Rahi, Deepak K.; Malik, Deepika
Abstract : Mushrooms are well known for their nutritional as well as therapeutic values worldwide. Interest in mushrooms has peaked because immunity and cellular protection are important issues for health conscious consumers and for those individuals who are dealing with serious health issues. Mushrooms generally belong to Basidiomycetes which harbors numerous mushroom species with diversity of metabolites of nutraceutical and therapeutic significance. They have been reported to be the most valuable ones for humans. Investigations on the therapeutic and nutritional properties of mushrooms are underway throughout the world. Researchers are providing crucial data on the array of bioactive compounds found within these fascinating fungi. People are now accepting mushrooms more as food and food supplements. Various academic and research institutes are all involved actively in research on bioactive metabolites of mushrooms. The present paper aims at reviewing the diversity of mushrooms and the types of metabolites especially of nutraceutical and therapeutic importance present in these mushrooms and their role as bioactive agents.